2000
DOI: 10.1063/1.1288016
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and optical properties of ionic ferrofluids based on nickel ferrite nanoparticles

Abstract: New ionic ferrofluids containing NiFe2O4 nanoparticles of size ⩽10 nm are investigated. The crystalline structure of the particles is probed by transmission electron microscopy and x-ray scattering. Static magnetization and field-induced birefringence measurements are performed on three samples differing by particle volume fraction. Cross analyzing of the results of those two types of macroscopic tests completely rejects a simple single-domain particle model but readily supports the two-component scheme of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…Such particles are generally termed as the core-shell nanoparticles, where the core spins behave like ferromagnetic or ferrimagnetic, and the shell is composed of disordered or canted spins. Hasmonay et al [9] and Jaing et al [10] explained the observed decrease in the saturation magnetization of NiFe 2 O 4 nanoparticles with the reduction in particle size on the basis of core-shell morphology and the surface effects arising from the noncollinearity of the magnetic moments on the surface, respectively. Later, Š epelák et al [11] and Jacob and Abdul [12] found that the nanostructured NiFe 2 O 4 sample having the lower grain size showed structural deviation from inverse spinel to mixed spinel structure as a result of interchange of cations between the A-and B-sites.…”
Section: Introductionmentioning
confidence: 97%
“…Such particles are generally termed as the core-shell nanoparticles, where the core spins behave like ferromagnetic or ferrimagnetic, and the shell is composed of disordered or canted spins. Hasmonay et al [9] and Jaing et al [10] explained the observed decrease in the saturation magnetization of NiFe 2 O 4 nanoparticles with the reduction in particle size on the basis of core-shell morphology and the surface effects arising from the noncollinearity of the magnetic moments on the surface, respectively. Later, Š epelák et al [11] and Jacob and Abdul [12] found that the nanostructured NiFe 2 O 4 sample having the lower grain size showed structural deviation from inverse spinel to mixed spinel structure as a result of interchange of cations between the A-and B-sites.…”
Section: Introductionmentioning
confidence: 97%
“…NiFe 2 O 4 finds various applications such as gas-sensor, magneticfluids, catalysts, magnetic storage systems, photomagnetic materials, magnetic resonance imaging [1][2][3][4][5][6]. Various methods have been established to prepare NiFe 2 O 4 nanoparticles, such as sol-gel method, reverse micelle, polymer assisted co-precipitation method, shock wave synthesis, combustion reaction, sonochemical process, hydrothermal methods, polymer-pyrolysis method, citrate precursor techniques and reverse micro emulsion process [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…the apparent M f.s could be less than ϕ v M p.s , or M f.s /ϕ v < M p.s , 6,12 where M f.s /ϕ v is termed the reduced magnetization of the ferrofluids and presents the effective magnetization of the solid phase. 13 For surface ferrofluids, this loss is assumed to arise from a chemical reaction between the surfactant and ferrite nanoparticles, but no structural or magnetic evidence exists to confirm this hypothesis. 6 Though it has been known that the spins in the surface being canted or the spins close to the surface to be pinned by surfactant molecules would result in the less saturation magnetization of nanoparticles M p.s than that of the bulk M b.s , 14,15 the arising of loss in ferrofluid magnetization is still no clear due to experimental diffcult.…”
Section: Introductionmentioning
confidence: 99%